Black carrot pomace as a source of polyphenols for enhancing the nutritional value of cake: An in vitro digestion study with a standardized static model. (April 2017) - Kamiloglu, Senem; Ozkan, Gulay; Isik, Hanife; Horoz, Ozge; Van Camp, John; Capanoglu, Esra
Abstract: Black carrot pomace (BCP), an industrial by-product of juice processing, is a promising source of polyphenols, in particular anthocyanins. In the present study, we investigated the digestive stability of polyphenols from BCP enriched cakes and monitored changes in their antioxidant capacity using a standardized static in vitro digestion model. Results showed that although enrichment of cake flour with BCP at levels of 50 g/kg, 100 g/kg and 150 g/kg caused a dose-dependent increase in anthocyanins (72–267 μg/g dw), phenolic acids (49–148 μg/g dw), total phenolics (54–202 mg GAE/100 g dw) and total antioxidant capacity (21–129 to 153–478 mg TE/100 g dw) for undigested samples, there was no statistical difference between the 100 g/kg and 150 g/kg BCP enriched sample ( p  > 0.05) after digestion. During the simulated bucal and gastric digestion the amount of anthocyanins and phenolic acids were reduced significantly (46–74% and 35–65%, respectively) ( p  < 0.05), whereas no anthocyanins were detected after simulated intestinal digestion. On the other hand, significant increases in total phenolic content and total antioxidant capacity were obtained after simulated gastric and intestinal digestion (up to 5- and 12-fold respectively). Highlights: Enrichment of cake with pomace caused a dose-dependent increase in polyphenols. During simulated bucal and gastric digestion amount of polyphenols were reduced. No anthocyanins were detected after simulated intestinal digestion. After simulated digestion, total antioxidant capacity increased significantly.